Formulation, Sensory, and Nutritional Characterization of Snack Bars Made from Moringa (Moringa oleifera) and Lumi-Lumi Fish (Harpodon nehereus) - Willi Yanti Rumapea; Hanif Muchdatul Ayunda; Safrida Safrida; Irzal Fanany (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2025)
Moringa oleifera leaves and Lumi-lumi (Harpodon nehereus) contain beneficial nutrients for the human body. The potential utilization of both materials as fortifying agents can improve the nutritional content of snack bars. This research aims to analyze the influence of moringa flour and lumi-lumi fish formulation on the sensory and chemical characteristics of snack bar products. The research design employed an experimental design with a Completely Randomized Design (CRD) involving three treatments: P1 (12 g moringa leaves + 30 g lumi-lumi), P2 (21 g + 30 g), and P3 (30 g + 30 g). Each treatment underwent proximate and organoleptic testing with 74 untrained panelists. The results showed significant differences in color and taste indicators between formulations (p-value <0.001 and 0.035), but no significant differences in aroma and texture (p-value 0.210 and 0.118). Formulation P1 was the most preferred by panelists. Its nutritional content includes 17.58% water, 2.78% ash, 22.18% fat, 2.83% protein, and 56.60% carbohydrates. In conclusion, snack bars made with a combination of moringa flour and lumi-lumi may serve as an acceptable alternative for meeting community macronutrient needs and support local food diversification.